The role of medium-frequency pulsed electrotherapy in patients with postoperative ileus after gynecological surgery - Ji, Jiazhen; Wu, Haixia; Huang, Xiaopei; Yang, Shouhua (Frontiers in Surgery, 2026)
ObjectiveTo investigate whether medium-frequency pulse electrical therapy can effectively shorten the duration of postoperative ileus in gynecological patients.MethodsClinical data from 126 eligible gynecological surgery patients from January 2024 to June 2024 were analyzed. Patients were grouped based on whether they received medium-frequency pulse electrical therapy and the initiation time of the therapy. Postoperative time to first flatus was compared between groups.ResultsThere was no statistically significant difference in the time to first anal exhaust between patients who received medium-frequency pulsed electrotherapy and those who did not (P = 0.36). Similarly, no significant difference was observed based on the timing of initiation of medium-frequency pulsed electrotherapy (P = 0.70).ConclusionMedium-frequency pulse electrical therapy shows no significant effect in shortening the duration of postoperative ileus in gynecological patients.